In-Silico Study Of Bioactive Compounds In Bawang Dayak (Eleutherine palmifolia (L) Merr.) Bulbs On The Main Protease Receptor Of COVID-19 (6LU7) As A Candidate For SARS-CoV-2 Antivirus Drug - Ulfa Dwi Septiana; Septyaningtyas Eka Wulandari; Nabila Kamalia; Tiara Anjelina Hezni; Mohammad Rofik Usman; Lindawati Setyaningrum (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2025)
: The COVID-19 viral disease is a new name given by the World Health Organization (WHO) to patients with the novel COVID-19 virus infection which was first reported from the city of Wuhan, China at the end of 2019. The COVID-19 pandemic is still a major problem in the world health. One antiviral regimen that is widely used to treat moderate to severe Covid- 19 patients is favipiravir. Many studies discuss alternative antiviral therapy for COVID-19 patients from active compounds contained in plants. One of the medicinal plants that has an antiviral effect on CoV-2 is Dayak onion (Eleutherine Palmifolia (L.) Merr). Consuming herbal plants can increase the body's immunity as the main key in preventing the Sars-Cov-2 virus. Purpose: This research aims to determine the effect of anchoring the active compound of Dayak onion bulbs on the growth of the corona virus on the main protease receptor for Covid 19 (6LU7). Methods: This type of research uses a molecular docking research method which consists of docking validation stages, a docking process and continues with docking visualization using Discovery Studio Visualizer and PyRx combined with Autodocktool Results: The results of the molecular docking simulation show that the Lysine sulfate compound has the lowest binding affinity value compared to Favipiravir, namely -4.75 kcal/mol with a Ki value of 96.41 μM and has the same interaction as the positive control ligand on the hydrophobic bond of MET A:165